'I can't bear the thought that he might not recognise me': Personal narratives as a site of identity work in the online Alzheimer's support group. (9th September 2016) - Kruk, Bartłomiej
Abstract : Narrative of personal experience, as a subjective interpretation of a set of events, constitutes a particularly fertile site for the construction of identity. It enables the teller to voice and (re-)organize disruptive phenomenological experiences, socialize emotions or forge interpersonal relations. Consequently, the narrator is able to access various facets of their identity and 'bring multiple, partial selves to life' (Ochs and Capps 1996: 19). Informed by the methods and insights of computer-mediated discourse analysis, conversation analysis and membership categorization analysis, and positioning narrative as a situated practice within social interaction, this paper scrutinizes publicly accessible data (15 forum threads) nested within a UK-based online Alzheimer's support group to demonstrate how Alzheimer's patients' family caregivers co-construct their sense of self when disclosing morally delicate aspects of their identities. The analysis demonstrates that the discursive space of the online support group encourages caregivers to disclose disruptions of predicates and activities associated with the 'family' membership categorization device. It also shows that the medium-afforded mode of engagement enables caregivers to gradually incorporate their unveiled aversive experiences into their autobiographical flow, with the help of other participants' responses which normalize these category disruptions.